Using Eye Tracking Method and Video Record In Usability Test of Educational Softwares and Gender Effects - Tonbuloglu, Ismail (ELSEVIER SCIENCE BV, 2013)
The research examines the usability of gender factor which is important educational softwares. Math educational software is used in the research and software's level is primary education. Used method in the research is ease study with eye-tracking and video record. Eye-tracking technology, screen captures, mouse and keyboard movies and one-way mirror observation used in the research. While students doing their task the application area, students behaviors have been recorded by camera. Study group is consist of six primary education's student. This student's eye movements to be examined while they used the software. The areas are defined where the students looked the longest and the most frequent in the educational software's interface. Heatmap, scan path and fixation count analyzes are used in the research. Usability researches which used eye-tracking method are limited in Turkey. This research will contribute the literature for developing primary educational softwares. Findings to be discussed and overtured for the educational softwares. (C) 2013 The. Authors. Published by Elsevier Ltd.
Keywords: Eye tracking; human computer - interaction; usability test; educational software; video record; Education & Educational Research